Experimental and Theoretical Research on the Compression Performance of CFRP Sheet Confined GFRP Short Pipe - Feng Li; Qilin Zhao; Li Chen; Guojian Shao (The Scientific World Journal)
The axial compressive strength of unidirectional FRP made by pultrusion is generally quite lower than its axial tensile strength. This fact decreases the advantages of FRP as main load bearing member in engineering structure. A theoretical iterative calculation approach was suggested to predict the ultimate axial compressive stress of the combined structure and analyze the influences of geometrical parameters on the ultimate axial compressive stress of the combined structure. In this paper, the experimental and theoretical research on the CFRP sheet confined GFRP short pole was extended to the CFRP sheet confined GFRP short pipe, namely, a hollow section pole. Experiment shows that the bearing capacity of the GFRP short pipe can also be heightened obviously by confining CFRP sheet. The theoretical iterative calculation approach in the previous paper is amended to predict the ultimate axial compressive stress of the CFRP sheet confined GFRP short pipe, of which the results agree with the experiment. Lastly the influences of geometrical parameters on the new combined structure are analyzed.